Desenvolvimento e validação de método cromatográfico para avaliação de potência de eritropoietina humana recombinante. Correlação com o ensaio biológico - Barth, Thiago (2007)
Erythropoietin is a glycoprotein which stimulates the erythropoiesis, clinically used for the treatment of renal anaemia. The biological and chromatographic methods for the potency evaluation of recombinant human erythropoietin (rhEPO) in pharmaceutical products were validated in the present work. The normocythaemic mice bioassay was carried out in female BALB/c strain, with multiple injections schedule and reticulocytes counted by automated flow cytometry. The dose-response curve was linear (r2=0.9708) in the concentration range of 1 to 64 IU/mL. A reversed-phase liquid chromatography method (RP-LC) was developed and validated using a Jupiter C4 column (250 mm x 4.6 mm), maintained at ambient temperature (25°C). The mobile phase A consisted of 0.1% trifluoroacetic acid (TFA) and mobile phase B consisted of 0.08% TFA:acetonitrile (30:70, v/v), run in linear gradient: 0.1-60 min, 0.1-100% of B at flow rate of 0.5 mL/min with detection at 280 nm. The chromatographic separation was obtained within 60 min and it was linear (r2=0.9997) in the concentration range of 10-150 μg/mL. The procedures were validated evaluating parameters such as, the specificity, linearity, precision, accuracy, robustness, and limit of quantitation, as well as, the limit of detection evaluated in the validation of the chromatographic method. The methods were applied for the potency evaluation of the alfa and beta rhEPO in pharmaceutical products, which were analysed by the chromatographic method and compared to the bioassay showing mean differences between the estimated potencies of 11.2% higher for the RP-LC. The alternative established represents a contribution towards the replacement of the animals improving the quality control and assuring the safety and efficacy of the biological product.